DSN-MUI FATWA IN DIGITAL BANKING: ADDRESSING THE CHALLENGES OF THE SHARIA ECONOMY IN THE 5.0 ERA AND ITS PROSPECTS IN THE FUTURE - Vidya Wahyu Prihatanti; Iskandar Ritonga; Aditya Surya Nanda (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
This study examines the strategic role of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) fatwas in governing the transformation of Islamic banking in the era of the 5.0 digital economy. While digitalization offers significant opportunities for Islamic financial institutions, it simultaneously demands legal certainty and strict compliance with Sharia principles. This research employs a qualitative approach through an in-depth literature review of DSN-MUI fatwas, regulations issued by the Financial Services Authority (OJK) and Bank Indonesia, as well as relevant scholarly sources on Islamic digital banking. The findings indicate that DSN-MUI fatwas function as a Sharia backbone in legitimizing digital financial services, including Islamic mobile banking, QRIS-based payments, Islamic e-money, digital financing, and online gold transactions. Beyond serving as normative guidelines, the fatwas also enhance public trust and stimulate responsible innovation aligned with the objectives of maqasid al-sharia. This study proposes a four-layer conceptual model—normative, technological, institutional, and impact layers—that positions fatwas at the core of the Islamic digital banking ecosystem. Although the prospects are highly promising, key challenges remain, including low levels of Islamic digital financial literacy, inadequate technological infrastructure, and the gap between rapid technological innovation and the issuance of adaptive Sharia rulings